Evaluasi Status Hara N, P, K Berdasarkan Toposekuen pada Tanah Lahan Cengkeh di Desa Puulemo Kecamatan Lembo Kabupaten Konawe Utara - Ramadhani, Nia; Rembon, Fransiscus S; Namriah, Namriah; Ginting, Sahta; Zulfikar, Zulfikar; Resman, Resman (Jurnal Agroteknologi (Agronu), 2024)
This research was carried out on a clove plantation in Puulemo Village, Lembo District, North Konawe Regency from June to July 2022. The purpose of this study was: to determine the nutrient status of different toposequences on community clove plantation in Puulemo Village, Lembo District, North Konawe Regency. The method used in the field is a survey method based on toposequence. Soil samples were taken by purposive sampling at three points, namely the top, middle and bottom of the slope with a depth of 0-30 cm and 30-60 cm. The samples were brought to the laboratory for analysis of the content of pH, Organic-C, nitrogen nutrients, phosphorus, soil potassium and soil CEC. The results showed that the assessment of some soil chemical properties in clove soil based on toposequences in Puulemo Village, Lembo District, North Konawe Regency, it can be stated that the total-N content in layers 0-30 cm and 30-60 cm were classified as moderate, available-K and available-P were classified as very low, pH values were classified as acidic, organic-C content was classified as very low and CEC content was classified as moderate at the top and bottom. in the middle and bottom at the 0-30 cm layer is classified as moderate while at the 30-60 cm layer it is classified as low.Keywords: Clove plant soil, nutrient status, toposekuen